2014
DOI: 10.1177/1753495x14533534
|View full text |Cite
|
Sign up to set email alerts
|

First reported case of ganglioneuroblastoma in pregnancy and a review of the literature

Abstract: Ganglioneuroblastoma is a variant of neuroblastoma tumours with mature ganglion cell differentiation which occurs commonly in cervical, mediastinal and retroperitoneal locations. Approximately 90% of ganglioneuroblastomas are seen in children younger than five years old. There are 50 adult cases of ganglioneuroblastomas reported to date. Our patient is the 51st case and she is the first to be diagnosed in pregnancy. Our patient's tumour site was the thoraco-abdominal retroperitoneal space adjacent to her kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…[ 2 ] It has been reported that ganglioneuroblastoma is seen most commonly during early childhood, especially in children under the age of 5 years with equal occurrence in males and females. [ 4 , 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] It has been reported that ganglioneuroblastoma is seen most commonly during early childhood, especially in children under the age of 5 years with equal occurrence in males and females. [ 4 , 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioneuroblastomas are extremely rare in adults, with only about 50 cases documented in people over the age of 20, and only five cases observed in the adult brain [7]. According to the present authors' knowledge, there are no reports in the literature of ganglioneuroblastoma presenting during pregnancy [8].…”
Section: Discussionmentioning
confidence: 66%
“…When diagnosing GNB, its clinical presentations are generally non-specific. Among the 104 reported cases, symptoms predominantly arose from compression by the primary or metastatic lesions ( 8 , 35 , 47 , 60 , 62 , 65 ). Some GNB cases with endocrine activity presented with endocrine-related symptoms such as diarrhea and malaise ( 4 , 15 , 36 , 49 , 77 ).…”
Section: Discussionmentioning
confidence: 99%